Pengembangan Perangkat Lunak Playon Sebagai Platform Untuk Sewa Dan Menyewa Tempat Olahraga Berbasis Web - Aang Muammar Zein; Bayu Priyambadha; Denny Sagita Rusdianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In this modern era, information technology has developed very rapidly. So that it affects the strength of the business sector, including the sports rental business. Now, to implement adequate information technology, small and large sports venues do not need to worry about allocating large amounts of funds. With the aim of making a profit and being able to compete in a wider market. One of them is using online-based information technology called e-commerce. The development of e-commerce is also accompanied by the development of payment gateways. The combination of e-commerce and payment gateways is expected to be a solution to the problems that exist in the sports rental business that is currently happening. The first problem that occurs is that there is a buyer who finds it difficult to find a sporting place around him in accordance with his wishes. The second problem is the recording of sports booking transactions that are still done manually so that the owner of a sports venue often has difficulty managing the transactions that are in the place of his sport. Because the problem above, PlayOn software was developed. With the leasing business process between the owner of the gym to the customer (B2C) and the customer to the customer (C2C). With the creation of this software, the hope of the above problems can be resolved. The system has been tested by unit testing, integration testing, and validation testing and producing a 100% valid value. In testing compatibility in getting the results that the software can be run there are all types of browsers and Android and iOS devices.